Respuesta :

3. First factor [tex]\cos^6A-\sin^6A[/tex] as a difference of cubes:

[tex]\cos^6A-\sin^6A=\underbrace{(\cos^2A-\sin^2A)}_{\cos2A}(\cos^4A+\cos^2A\sin^2A+\sin^4A)[/tex]

For the remaining group, apply the double angle identity.

[tex]\cos^2A=\dfrac{1+\cos2A}2[/tex]

[tex]\sin^2A=\dfrac{1-\cos2A}2[/tex]

[tex]\implies\begin{cases}\cos^4A=\left(\dfrac{1+\cos2A}2\right)^2=\dfrac{1+2\cos2A+\cos^22A}4\\\\\cos^2A\sin^2A=\dfrac{(1+\cos2A)(1-\cos2A)}4=\dfrac{1-\cos^22A}4\\\\\sin^4A=\left(\dfrac{1-\cos2A}2\right)^2=\dfrac{1-2\cos2A+\cos^22A}4\end{cases}[/tex]

[tex]\implies4(\cos^6A-\sin^6A)=\cos2A[(1+2\cos2A+\cos^22A)+(1-\cos^22A)+(1-2\cos2A+\cos^22A)][/tex]

[tex]=\cos2A(3+\cos^22A)=\cos^32A+3\cos2A[/tex]

5. seems rather tricky. You might want to post another question for that problem alone...

6. Factorize the left side as a sum of cubes:

[tex]\cos^320^\circ+\sin^310^\circ=(\cos20^\circ+\sin10^\circ)(\cos^220^\circ-\cos20^\circ\sin10^\circ+\sin^210^\circ)[/tex]

From here we have to prove that

[tex]\cos^220^\circ-\cos20^\circ\sin10^\circ+\sin^210^\circ=\dfrac34[/tex]

We can write everything in terms of sine:

[tex]\cos^220^\circ=(1-2\sin^210^\circ)^2=1-4\sin^210^\circ+4\sin^410^\circ[/tex] (double angle identity)

[tex]\cos20^\circ\sin10^\circ=\dfrac{\sin30^\circ-\sin10^\circ}2=\dfrac14-\dfrac12\sin10^\circ[/tex] (angle sum identity)

After some simplifying, we're left with showing that

[tex]4\sin^410^\circ-3\sin^210^\circ+\dfrac12\sin10^\circ=0[/tex]

or

[tex]4\sin^310^\circ-3\sin10^\circ+\dfrac12=0[/tex]

This last equality follows from what you could the triple angle identity for sine,

[tex]\sin3x=3\sin x-4\sin^3x[/tex]

ACCESS MORE